Pengaruh Luas Lahan, Modal dan Harga Jual Terhadap Pendapatan Petani Padi Di Desa Sarimulyo Kecamatan Cluring - Anja Liutik Pesra; Erlin Susilowati; Driyanto Wahyu Wicaksono (Politeknik Negeri Banyuwangi Jl. Raya Jember km. 13 Labanasem, Kabat, Banyuwangi, Jawa Timur (68461) Telp. (0333) 636780, 2026)
Rice farmer income is one indicator of farming success that is influenced by various factors, such as land area, capital, and selling price of the harvest. Sarimulyo Village, Cluring District, is an agricultural area with the majority of the population working as rice farmers. This study aims to analyze the effect of land area, capital, and selling price on the income of rice farmers in Sarimulyo Village, Cluring District, both partially and simultaneously. The study used a quantitative method with a descriptive approach. The research sample consisted of 83 rice farmers determined using the Slovin formula and selected through a purposive sampling technique. Data analysis was carried out using multiple linear regression with the help of SPSS version 27. The results showed that land area had a positive and significant effect on farmer income with a significance value of 0.000 and a regression coefficient of 1.232. Selling price also had a positive and significant effect with a significance value of 0.005 and a regression coefficient of 2.741. Meanwhile, capital did not have a significant effect on farmer income with a significance value of 0.170 and a regression coefficient of -0.176. Simultaneously, land area, capital, and selling price significantly influence rice farmers' income. The coefficient of determination (R²) of 0.857 indicates that 85.7% of the variation in farmers' income can be explained by these three variables. The novelty of this study lies in the use of dummy variables to analyze land ownership status.